Assessment of Antagonistic Effect of Alcoholic Extract from Cyanophyta (Spirulina Platensis) Against Several Human and Plant Derived Pathogenic Fungi - Raghad J. Fayyad1, Rasha Saad Nuaman2, Noor T. Hamdan3, Rasha Saatam Hameed4, Sara A. J. Maliki5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Blue-green algae have been proved to producing different bioactive compounds. For this reason Spirulina platensis isolates have been used in the present study as a biocontrol agent against several human and plant pathogenic fungi. Current study was aimed to investigate the use of crude extract of Spirulina platensis as antifungal agent by determining the antagonistic activity of methanolic extract of Spirulina platensis against several human and plant pathogenic fungi. Also, to determine the antifungal phytochemicals within algal alcoholic extract through GC-mass analysis. Method: Four different concentrations of alcoholic extract were prepared (100,75, 50 and 25mg/ml) from algal isolates and their antagonistic activity was investigated against molds isolated from spoiled fruits (two isolates of Aspergillus niger, Aspergillus flavus, Mucor sp. and Botrytis sp.) and against several Candiada spp. (Candida albicans, Candida glurbrate, Candida fameta, Candida lustrans) which were isolated from different clinical sources. Results: The results showed that algal extract displayed wide range of antagonistic activity against tested fungi depending on applied algal extract concentration and tested fungal species. Also, GC-Mass data analysis had been performed for algal extract and 36 different bioactive chemicals have been identified including eight compounds authenticated as having antifungal activity. Conclusion: Spirulina could be used as alternative drug to treat Candida sp. infections as well as added to food industries to enhance their nutritional value and simultaneously decreasing the possibility of food spoilage by molds.